Western boundary dynamics and overturning circulation in the Subpolar North Atlantic - Liu, Yingjie (CCSD, 2022)
The Atlantic Meridional Overturning Circulation (AMOC) is an essential component of the climate system due to its vital role in the global distribution of heat, carbon, and water masses. The downwelling of North Atlantic surface waters connecting the upper and lower AMOC limbs is an essential yet vulnerable partof this global circulation. This downwelling partly occurs along continental boundaries. This dissertation presents an extended observational investigation on the quantification of Eulerianmean downwelling along the continental slopes of the North Atlantic subpolar gyre (SPG) and an examination of the underlying mechanisms, with an emphasis on the role of mesoscale eddies. A volume budget of the SPG boundary reveals a total Eulerian-mean (2002-2019) downwelling of -4.41±0.96 Sv at 1300 m depth between Denmark Strait and Flemish Cap, with the barotropic transport (BT) contributing 2.66±0.40 Sv and the baroclinic transport (BC) contributing 1.75±0.43 Sv. To investigate the processes that cause the BC boundary downwelling, i.e., the boundary heat loss and associate along-boundary density gradient, the long-term mean heat budget of the boundary current system is studied. Both lateral heat fluxes, driven by the boundary current/mesoscale eddies, and air-sea heat flux play significant roles in the boundary heat loss. In a Lagrangian framework, it is found that cross-shore eddy propagation generally cools the SPG boundary. La circulation méridienne de retournement de l'Atlantique (AMOC) est une composante essentielle du système climatique en raison de son rôle vital dans la distribution globale de la chaleur, du carbone et des masses d'eau. La descente des eaux de surface de l'Atlantique Nord reliant les branches supérieure et inférieure de l'AMOC est une composante essentielle mais vulnérable de cette circulation globale. Le transport vertical associé se produit en partie le long des frontières continentales. Cette thèse présente une étude observationnelle étendue sur la quantification du « downwelling » ...